2013
DOI: 10.1002/acr.21876
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Safety, and Efficacy of Abatacept Administered Subcutaneously With or Without Background Methotrexate in Patients With Rheumatoid Arthritis: Results From a Phase III, International, Multicenter, Parallel‐Arm, Open‐Label Study

Abstract: Objective. To evaluate the impact of concomitant methotrexate (MTX) on subcutaneous (SC) abatacept immunogenicity, and to assess safety and efficacy.Methods. This phase III, open-label study had a 4-month short-term (ST) period and an ongoing long-term extension (LTE) period. Rheumatoid arthritis patients were stratified to receive SC abatacept (125 mg/week) with (combination) or without MTX (monotherapy), with no intravenous loading dose; patients receiving monotherapy could add MTX in the LTE period. Immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 26 publications
4
39
1
Order By: Relevance
“…There was a tendency to an increase in autoantibodies if one to two doses of abatacept were missed. No relationship was found between the antibodies and clinical response or adverse events (category A evidence44). …”
Section: Abatacept (Blocking Costimulation Of T Cells At the Cd28–cd8mentioning
confidence: 91%
“…There was a tendency to an increase in autoantibodies if one to two doses of abatacept were missed. No relationship was found between the antibodies and clinical response or adverse events (category A evidence44). …”
Section: Abatacept (Blocking Costimulation Of T Cells At the Cd28–cd8mentioning
confidence: 91%
“…Finally, we retained 16 articles. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] All of these trials included 4975 patients, representing a total of 6764 patient-years followed up and including 3866 patient-years in the 'bDMARD and methotrexate' group and 2898 patient-years in the 'bDMARD alone' group.…”
Section: Article Selection Processmentioning
confidence: 99%
“…To the contrary, repeated-dose rat and monkey studies have shown that intramuscular dosing with interferon b-1a (Rebif 1 ) was associated with higher ADA titers compared with IV dosing (Ponce et al 2009). For a different rh therapeutic protein (abatacept), SC/IV immunogenicity differences were not observed in patients (Fathallah, Bankert, and Balu-Iyer 2013;Keystone et al 2012;Nash et al 2013), but SC administration elicted greater ADA titers compared with IV dosing in rat preclinical studies (Srinivas et al 1997). For adalimumab in monkeys, IV dosing was associated with higher ADA titers compared with SC dosing (Ponce et al 2009).…”
Section: Ada In Humans Administered Therapeutic Proteinsmentioning
confidence: 99%
“…Immunogenicity can also be affected by the mechanism of action of the drug itself (Brennan et al 2010;Srinivas et al 1997). For example, abatacept, a human IgG constant region of immunoglobulin (Ig) molecule (Fc) fused with the extracellular domain of cytotoxic T-lymphocyte antigen 4 (CTLA-4), is highly immunosuppressive, and low doses are associated with ADA development, while higher doses do not elicit ADA, in rat preclinical studies (Fathallah, Bankert, and Balu-Iyer 2013;Keystone et al 2012;Nash et al 2013). When ADA neutralize or accelerate clearance of the rh therapeutic protein, they may be associated with altered PK and/or PD properties of the therapeutic protein; however, some ADA may have no discernible effect on PK/PD levels (Leach 2013;Ponce et al 2009;Rojas et al 2005).…”
Section: Ada In Monkeys On Preclinical Studies Of Therapeutic Proteinsmentioning
confidence: 99%